Un esquema de clasificación de las fuerzas que afectan el comportamineto orginal y creador - Stephenson, Robert W.; Stephenson, Matidle Kejner (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This article describes a possible reorganization of the research results on creative behavior. This conceptualization is based on the logical combinations that exist when the various forces that effect creative behavior and originality are analyzed in terms of (a) the model of access to the preconscious, (b) the model of numerical complexity, (c) the model of manipulation of the field, and (d) the model of cultural influence.